1997
DOI: 10.1161/01.str.28.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of Vasogenic Edema and Cytotoxic Edema Assessed by Quantitative Diffusion and T2 Magnetic Resonance Imaging

Abstract: T2 imaging can assess ischemic insults as well as ADC imaging, but only 3.5 hours after the onset of ischemia. Assessment of edematous swelling (approximately 24.5% of total infarcted volume) demonstrates that ADC and therefore T2 imaging detect all the tissue that will become infarcted approximately 7 hours after occlusion. The spread of ADC and T2 abnormalities would therefore stop at approximately 7 hours, and any further increase in volume observed on the images would be mainly due to edematous swelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
142
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(154 citation statements)
references
References 45 publications
11
142
1
Order By: Relevance
“…This assumption is supported by previous studies, which show that in humans the maximum evolution of vasogenic edema culminates at 24 to 48 hours (28). On the contrary, the vasogenic edema contribution in the first seven hours was found to be negligible in rats (20).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This assumption is supported by previous studies, which show that in humans the maximum evolution of vasogenic edema culminates at 24 to 48 hours (28). On the contrary, the vasogenic edema contribution in the first seven hours was found to be negligible in rats (20).…”
Section: Discussionsupporting
confidence: 81%
“…On the contrary, the vasogenic edema contribution in the first seven hours was found to be negligible in rats (20). The spread of ADC would thus stop at approximately seven hours and any further increase in volume would mainly be due to edematous swelling (28). These results in animals need to be clarified in human experiments, but measures of the DWI volume clearly must take into account the expansion of vasogenic edema, especially during the first 24 hours.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although we utilized a model of a focal ischemic insult, in which the cytotoxic edema appears to be predominant (Dijkhuizen et al, 1999;Loubinoux et al, 1997), it is possible that a vasogenic component of edema was also present. Studies of brain edema have shown that the BBB remains intact during the first 6 h following MCA occlusion and reperfusion (Hatashita et al, 1988;Iannotti and Hoff, 1983).…”
mentioning
confidence: 99%
“…Correction for edema-induced midline shift in hemispherical volume was incorporated into infarct volume calculations as described previously. 2,20 Neurobehavioral Assessment Neurobehavioral assessment was performed by a neurologic interventional radiologist before the procedure at 24 h and 7 days following embolization. A simple 12-point canine neurobehavior scoring system (Table 1), including assessments of motor function, consciousness, head turning, circling and hemianopsia, was adapted for the canine ischemic stroke models.…”
Section: Mr Scanningmentioning
confidence: 99%